2020
DOI: 10.1002/ctm2.257
|View full text |Cite
|
Sign up to set email alerts
|

The roles of exosomes in cancer drug resistance and its therapeutic application

Abstract: 1. The mechanisms of exosome-induced cancer drug resistance are elaborated. 2. The potential therapeutic application of exosomes is discussed in great detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 138 publications
(265 reference statements)
0
59
0
Order By: Relevance
“…Exosomes are a subset of extracellular vesicles with a diameter ranging from 40nm to 160nm, which can mediate cell communication in physiological and pathological conditions via transferring specific cargos (nucleic acid or protein) [ 46 ]. Recently, it is reported that miRNAs carried by exosomes derived from drug-resistant cells can confer the resistant ability to drug-sensitive ones [ 47 ]. For example, CSCs and resistant cancer cells can secrete exosomal miR-155, which induces the EMT process to enhance the resistance to chemotherapy of breast cancer [ 48 ].…”
Section: Mirna-mediated Emt and Cscs In Chemotherapy Resistancementioning
confidence: 99%
“…Exosomes are a subset of extracellular vesicles with a diameter ranging from 40nm to 160nm, which can mediate cell communication in physiological and pathological conditions via transferring specific cargos (nucleic acid or protein) [ 46 ]. Recently, it is reported that miRNAs carried by exosomes derived from drug-resistant cells can confer the resistant ability to drug-sensitive ones [ 47 ]. For example, CSCs and resistant cancer cells can secrete exosomal miR-155, which induces the EMT process to enhance the resistance to chemotherapy of breast cancer [ 48 ].…”
Section: Mirna-mediated Emt and Cscs In Chemotherapy Resistancementioning
confidence: 99%
“…As key contributors to cell–cell communication, exosomes have been implicated in the induction of anti-tumor drug resistance [ 89 , 90 ]. For instance, they transfer functional P-glycoprotein as they bind to drug-sensitive recipient cells, a key process in the induction of signal pathways necessary for drug resistance in recipient cells [ 91 , 92 ]. Drug resistance to cisplatin, a platinum-based DNA damage drug administered intravenously to treat many cancers, has been demonstrated in NSCLC.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…EVs bind to target cells and initiate signal transduction through receptor-ligand interactions or internalize through endocytosis [ 96 ]. EVs mediate cancer cell sensitivity to chemotherapy and radiotherapy, and are promising strategy in liquid biopsy for cancer diagnosis and predictive markers [ 97 , 98 ]. The exchange of EVs between immune cells affects innate immunity and adaptive immunity [ 99 ].…”
Section: Tumor Microenvironment Related Biomarkersmentioning
confidence: 99%